THE SCATTER OF TIME-DELAYS IN SHEAR-WAVE SPLITTING ABOVE SMALL EARTHQUAKES - Crampin S.; Peacock Sh.; Gao Yu.; Chastin S. (My University, 2004)
Measurements of time-delays in seismic shear-wave splitting above small earthquakes typically display a scatter of often as much as ±80 per cent about the mean. Changes in the average time-delay appear to be related to changes of stress, but applications of this potentially powerful tool have been handicapped by the previously inexplicable scatter in time-delays above earthquakes. In contrast, measurements of shear-wave time-delays in controlled-source exploration seismics are typically well controlled and display little scatter. Previous estimates of possible causes of scatter cannot produce sufficient variation specifically above earthquakes. Here we show that 90°-flips in shear-wave polarizations due to fluctuating high pore-fluid pressures on seismically-active fault planes are the most likely cause of the scatter.
Keywords: CRACK-CRITICAL SYSTEMS; CRITICALLY-HIGH PORE-FLUID PRESSURES; SCATTER IN TIME-DELAYS; SHEAR-WAVE SPLITTING; 90°-FLIPS